Os proprietários de escravos e a estrutura da posse na antiga freguesia de São Simão, 1835 - Lopes, Luciana Suarez (Estudos Econômicos (São Paulo), 2012)
This paper analyses the slaveholding structure in São Simão, a town northeast of São Paulo, using the manuscript known as lista nominativa of 1835. The objective is to analyze the structure of ownership of slaves in the region before the arrival of coffee. Apparently, the production structure formed in this period gave conditions, among other factors, for the rapid development of coffee cultivation during the second half of the nineteenth century, especially in the town of Ribeirão Preto, separated from São Simão in the early years of the 1870s. Ribeirão Preto, in the last decade of the nineteenth century, became one of the largest producers of coffee in the State of Sao Paulo.